Falsche Freunde - ein Hindernis im Fremdsprachenlernprozess nur in der Theorie oder auch in Praxis? - Kosturek, Kamila (Wydawnictwo Naukowe UAM, 2013)
This article discuses the results of a questionnaire on English-German false-friend pairs, carried out among four groups of respondents. The first three groups included Polish students of German and English Studies at the University of Rzeszow, while the last one consisted of native speakers of German. The respondents stated that their knowledge of false friends in both languages was good or even profound, however, the results obtained in the practical part of the questionnaire seemed to diverge from their declared knowledge. This suggests the need to pay greater attention to the phenomenon of false friends in foreign language teaching.
False friends – an obstacle to foreign language learning process only in theory or also in practice?
Keywords: false friends; foreign language learning; language interference